Clinical evidence inputs to comparative effectiveness research could impact the development of novel treatments. (May 2015) - Eber, Michael R; Goldman, Dana P; Lakdawalla, Darius N; Philipson, Tomas J; Pritchard, Daryl; Huesch, Marco; Summers, Nicholas; Linthicum, Mark T; Sullivan, Jeff; Dubois, Robert W
Aim: This study aims to analyze the impacts of a range of clinical evidence generation scenarios associated with comparative effectiveness research (CER) on pharmaceutical innovation.Materials & methods: We used the Global Pharmaceutical Policy Model to project the effect of changes in pharmaceutical producer costs, revenues and timings on drug innovation and health for the age 55+ populations in the USA and Europe through year 2060 using three clinical scenarios.Results: Changes in producer incentives from widespread CER evidence generation and use had varied but often large predicted impacts on simulated outcomes in 2060. Effect on the number of new drug introductions ranged from a 81.1% reduction to a 45.5% increase, and the effect on population-level life expectancy ranged from a 15.6% reduction to a 11.4% increase compared to baseline estimates.Conclusion: The uncertainty surrounding the consequences of increased clinical evidence generation and use on innovation calls for a carefully measured approach to CER implementation, balancing near-term benefits to spending and health with long-term implications for innovation.